Pemetaan Orthophoto Untuk Rencana Pembuatan Peta Rawan Longsor - Adkha Yulianandha Mabrur; Silvester Sari Sai; Fransisca Dwi Agustina (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Landslides are one of the natural disasters that often occur in Indonesia. The area can be seen geologically by having a hilly land surface with quite steep soil conditions. Several factors cause landslides such as rainfall, sloping slopes, soil type, and the presence of vibration. One region that is classified as a landslides prone area is Pandansari Village, Ngantang District, Malang Regency. This is because some areas of Malang Regency are hills with quite steep land slopes, erratic rainfall conditions and land used that is not under the type of soil. The process of data sampling and processing is carried out by utilizing photogrammetric mapping and Geographic Information Systems in identifying landslide disasters. The processed data is the result of the photogrammetric mapping, namely orthophoto and DEM which can later be used for the landslide identification process. The results of the research in the first year are in the form of orthophoto which will later be used as data for making landslide-prone maps for the Pandansari Village area, Ngantang District, Malang Regency, and landslide-prone maps by utilizing the required data parameters as supporting data for identifying the level of landslide susceptibility. This study will be useful for the of the Pandansari Villager, Ngantang District, Malang Regency to determine the level of vulnerability from low to very vulnerable class, so people can anticipate landslides.